Biliary excretion of cephalosporins in rats: influence of molecular weight. - Wright, W E (1980)
The biliary excretion of 18 cephalosporin derivatives with varying 3- and 7-substituents was examined in cannulated rats. In spite of the widely differing physical chemical properties imparted by the different structures, the dominant influence on the degree of biliary excretion was the molecular weight of the compound. Above a threshold molecular weight of about 450, biliary excretion increased in a generally progressive way, becoming the principal route of excretion of the higher-molecular-weight derivatives. Examples were found in which the molecular weight influence was modified but not abolished by specific substituents. Biliary excretion varied from less than 5% to greater than 90% of the dose. Interruption of bile flow resulted in an increase in urinary excretion. Biliary excretion may influence the evaluation of new cephalosporins in rodent models. Such influence must be considered when selecting candidate compounds intended for eventual use in humans, where the excretion pattern may be different from that in rodents.